Achieving partial nitrification and high lipid production in an algal-bacterial granule system when treating low COD/NH4–N wastewater. (June 2020) - Huang, Wenli; Liu, Dongfang; Huang, Weiwei; Cai, Wei; Zhang, Zhenya; Lei, Zhongfang
Abstract: Partial nitrification-Anammox process is an efficient and energy-saving method for nitrogen removal from low C/N wastewaters. In this study, partial nitrification was achieved in an algal-bacterial granular sludge system when treating low COD/NH4 –N (309.4 mg L −1 /213.6 mg L −1 ) wastewater under sunlight irradiation (RS ). Sunlight irradiation, algae growth and free nitrous acid (FNA) decreased the activity of ammonia oxidizing bacteria (AOB) by 25.7% and completely inhibited the activity of nitrite oxidizing bacteria (NOB), resulting in a NH4 –N removal efficiency of ≥99% and a nitrite accumulation efficiency of 96.5% in Rs. Compared with the control without sunlight irradiation (RC ), the algal-bacterial granules in RS produced 34.7% and 13.1% more proteins and polysaccharides, respectively, and exhibited a higher structure stability. The lipid content in the algal-bacterial granules was 68.7 mg g-SS −1, which was about 2.1 times higher than that in the granules from RC, making the algal-bacterial granule a value-added biomass. Meanwhile, the content of unsaturated fatty acid methyl esters increased remarkably due to the growth of algae ( Stigeoclonium, Scenedesmus and Navicula ). The combined stress of sunlight irradiation, algae growth and high FNA in RS only slightly lowered the relative abundance of Nitrosomonadaceae (AOB family) from 7.5% to 5.8%, while Nitrospiraceae (NOB family) was severely inhibited and became undetectable. Highlights: Partial nitrification was achieved in an algal-bacterial granular sludge system. Algal-bacterial granules exhibited greater stability and higher lipid productivity. Nitratation process was significantly inhibited by sunlight, algae and FNA. NOB was more sensitive and unfavorable than AOB in the new system. Stigeoclonium, Scenedesmus, Navicula were dominant algae in algal-bacterial granule.